2014
DOI: 10.1177/0013124514536440
|View full text |Cite
|
Sign up to set email alerts
|

Caring Is Not Enough

Abstract: The educational landscape for schools in the United States is continuing to shift with the arrival of refugee students with limited or interrupted formal education, especially at the secondary schools. As refugee students with limited or interrupted formal education (SLIFE) adjust to schools in the United States, they may experience acculturative stress, migration stress, and stress of learning a new language. Teachers play an essential role in providing support to help immigrant and refugee students adjust. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…As newly arrived migrant and refugee learners constitute a vulnerable group in many school settings, there is an expanding body of research exploring the role of schools in providing care and support for migrant and refugee learners (Borsch et al, in press;Hek, 2005;Kia-Keating & Ellis, 2007;Schachner et al, 2018). Teachers have been noted as well-placed to identify and refer vulnerable migrant and refugee learners to mental health services within and outside of school (Baak et al, 2020;Fazel, 2015;Fazel et al, 2016), and they have been observed to engage in substantial care work (Hos, 2016;Matthews, 2008;Norozi, 2019) often with limited support from school leadership or external support services (Häggström et al, 2020). This research highlights the importance of physical school spaces, with newly arrived migrant and refugee learners often relying on teachers' alternative means of communication to express care, and to read distress signals.…”
Section: Introductionmentioning
confidence: 99%
“…As newly arrived migrant and refugee learners constitute a vulnerable group in many school settings, there is an expanding body of research exploring the role of schools in providing care and support for migrant and refugee learners (Borsch et al, in press;Hek, 2005;Kia-Keating & Ellis, 2007;Schachner et al, 2018). Teachers have been noted as well-placed to identify and refer vulnerable migrant and refugee learners to mental health services within and outside of school (Baak et al, 2020;Fazel, 2015;Fazel et al, 2016), and they have been observed to engage in substantial care work (Hos, 2016;Matthews, 2008;Norozi, 2019) often with limited support from school leadership or external support services (Häggström et al, 2020). This research highlights the importance of physical school spaces, with newly arrived migrant and refugee learners often relying on teachers' alternative means of communication to express care, and to read distress signals.…”
Section: Introductionmentioning
confidence: 99%
“…B. Dooley 2009, Hos 2016, Miller et al 2005 Stanat et al 2005, Kowoll et al 2013. Solche Sommerlernangebote wurden, teils gezielt für lernschwächere Schüler:innen oder solche mit geringen Deutschkenntnissen, in einigen Bundesländern im Sommer 2020 als Reaktion auf die pandemiebedingten Schulschließungen angeboten (z.…”
Section: Lernunterbrechungen Im Kontext Der Sprachlichen Entwicklungunclassified
“…W ith English learners (ELs), particularly students with limited or interrupted formal education (SLIFEs), it is necessary for teachers to access students' existing repertoires of knowledge as a foundation for future learning and to teach in ways that reflect care for students' well-being and academic success (A. García & Gaddes, 2012;Hos, 2016). Instructional practices that take into account students' backgrounds while providing them opportunities to learn in a supportive environment ensure that students have access to comprehensible input (Krashen, 1985) needed for intellectual and linguistic development.…”
Section: Rebecca E Linaresmentioning
confidence: 99%